Regulasi Privasi Perlindungan Data Pasien Covid-19 - Riskha Dora Candra Dewi (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2022)
The public health crisis that occurred during the current COVID-19 pandemic has created pressure for some of the affected people. Therefore, the privacy of COVID-19 patient data needs to be protected by the government. The purpose of this study was to examine the Privacy Regulations for the Protection of COVID-19 Patient Data. This research is a literature review research or what is known as a literature review. This research was conducted by analyzing 6 articles published between 2020-2021 regarding the protection of data privacy for COVID-19 patients in several national and international journals. The results of the research analysis show that the potential for misuse of COVID-19 patient data can lead to discrimination and exclusivity of all parties involved, including an increase in excessive public fear. Thus, certain legal frameworks should be adopted to reduce the risk of misuse of personal data of COVID-19 patients.